Impact of COVID-19 on Clinical and Academic Urological Practice: A Survey from European Association of Urology Section of Uro-technology (2020)
Background: The unexpected coronavirus disease 2019 (COVID-19) pandemic has spread worldwide rapidly, developing into a global health crisis. At the same time, it has seriously impacted the daily activities in all the fields of urology. Objective: To better understand the impact of the COVID-19 pandemic on clinical, academic, and scientific activities as well as on the quality of life of urologists from the main centers in Europe. Design, setting, and participants: We conducted a survey using a 37-item questionnaire. The survey included three main sections: clinical practice, academic/ scientific activities, and personal/social quality of life. Outcome measurements and statistical analysis: A descriptive analysis was performed using the collected data. Results and limitations: A total of 107 representatives affiliated to different centers from 22 countries completed the survey. Clinical activities were affected in 54.2% of the centers, and 85.0% of the elective surgeries were cancelled. Of the urological departments, 64.5% were still performing minimally invasive surgery for malignant disease. In 33.6% of the hospitals, dedicated and specially equipped operating theaters for COVID-19–positive patients were not available. According to 72.9% of participants, COVID-19 had a substantial negative impact on academic activities, and 82.3% of the respondents agreed that their quality of life has been affected negatively by the pandemic. Finally, 92.5% of the participants believe that the pandemic will have a moderate to severe impact on the health system of their countries.